Cross-Cultural Adaptation, Validity, and Reliability of the Patient-Rated Michigan Hand Outcomes Questionnaire for Thai Patients - Jananya P. Dhippayom; Piyawat Trevittaya; Andy S. K. Cheng (Occupational Therapy International)
Introduction. The Michigan Hand Outcomes Questionnaire (MHQ) is a patient-rated hand outcome instrument. It is widely used in orthopedic and neurological conditions of the hands and upper limbs. To gain more knowledge on hand outcomes from a Thai patient perspective, an MHQ-Thai version is required. Purpose of the Study. The study is aimed at translating and cross-culturally adapting the MHQ into Thai and at examining the validity and reliability of the translated version. Methods. The Beaton protocol for cross-cultural adaptation of self-reported measures was used in the translation process. Three occupational therapists were asked to assess content validity while 30 participants were asked to fill in the questionnaire in order to assess construct validity, internal consistency, and test-retest reliability. Results. All six domains of the MHQ were translated into Thai without any major problems. However, items related to the characteristics of the patients were adapted to suit the Thai context. The MHQ-Thai version had good content validity (IOC 0.972). The construct validity revealed a low-to-high correlation between every subscale of the MHQ-Thai version. The intraclass correlation coefficient (ICC) of the test-retest reliability for the six domains ranged from 0.788 to 0.956, with excellent correlation (ICC = 0.953) for the total score. Cronbach’s alpha was 0.835 for the total score of the MHQ-Thai version, indicating good internal consistency. Discussion and Conclusions. MHQ was successfully cross-culturally adapted into Thai. The MHQ-Thai version is a valid and reliable instrument for evaluating the self-perception of Thai people who have hand and upper limb injuries.